Increased cross-education of muscle strength and reduced corticospinal inhibition following eccentric strength training. (6th August 2015) - Kidgell, D.J.; Frazer, A.K.; Rantalainen, T.; Ruotsalainen, I.; Ahtiainen, J.; Avela, J.; Howatson, G.
Highlights: Eccentric exercise modulates corticospinal inhibition of the untrained limb compared to concentric exercise. Eccentric contractions provide a greater stimulus for the cross-transfer of motor performance. Eccentric exercise could be used following unilateral injury to maximize the cross-transfer response. Abstract: Aim: Strength training of one limb results in a substantial increase in the strength of the untrained limb, however, it remains unknown what the corticospinal responses are following either eccentric or concentric strength training and how this relates to the cross-education of strength. The aim of this study was to determine if eccentric or concentric unilateral strength training differentially modulates corticospinal excitability, inhibition and the cross-transfer of strength. Methods: Changes in contralateral (left limb) concentric strength, eccentric strength, motor-evoked potentials, short-interval intracortical inhibition and silent period durations were analyzed in groups of young adults who exercised the right wrist flexors with either eccentric ( N  = 9) or concentric ( N  = 9) contractions for 12 sessions over 4 weeks. Control subjects ( N  = 9) did not train. Results: Following training, both groups exhibited a significant strength gain in the trained limb (concentric group increased concentric strength by 64% and eccentric group increased eccentric strength by 62%) and the extent of the cross-transfer of strength was 28% and 47% for the concentric and eccentric group, respectively, which was different between groups ( P  = 0.031). Transcranial magnetic stimulation revealed that eccentric training reduced intracortical inhibition (37%), silent period duration (15–27%) and increased corticospinal excitability (51%) compared to concentric training for the untrained limb ( P  = 0.033). There was no change in the control group. Conclusion: The results show that eccentric training uniquely modulates corticospinal excitability and inhibition of the untrained limb to a greater extent than concentric training. These findings suggest that unilateral eccentric contractions provide a greater stimulus in cross-education paradigms and should be an integral part of the rehabilitative process following unilateral injury to maximize the response.